Implementasi Gaya Kepemimpinan Demokratis Kepala Sekolah dalam Meningkatkan Kinerja Guru di MTsN 2 Pangandaran - Rama Aditya (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2025)
Management strategy is a plan that can guide managers in a directed manner The leadership of the school principal plays a very important role in the education system. The school principal is responsible not only for managing the school effectively but also for leading and motivating the staff, as well as interacting with students and parents. The issues in the background of this research relate to the implementation of democratic leadership styles on teacher performance, due to suboptimal use of teaching methods with students and low levels of teacher discipline. This study aims to understand the implementation of democratic leadership by school principals in enhancing teacher professionalism. Democratic leadership is a leadership style employed by principals in their efforts to improve teacher performance, including professionalism. This type of research is qualitative, using a qualitative descriptive research method. The data collection techniques used in the research include: observation, document study, and interviews with the principal, vice principal, and teachers. After obtaining the necessary data, the author describes and then analyses it. The results of the research conducted show that the implementation of democratic leadership by the school principal in improving teacher performance is going well. The strategies implemented include providing rewards, teacher discipline, coaching and training, high trust in subordinates, scheduled planning for professional development, and interventions in management and the learning process